In vivo evaluation of wheat (Triticum aestivum L.) cultivars for moisture stress - Tamiru, S; Ashagre, H (International Journal of Agricultural Research, Innovation and Technology, 2015)
In Ethiopia, wheat productivity is constrained by water stress especially at germination and seedling stage. The objective of this research was to determine the effect of moisture stress on bread wheat (Triticum aestivum) cultivars. Four wheat cultivars (Dandaa, Kubsa, Huluka and Local) were treated with six levels of water stress (0, 50, 100, 150, 200 and 250 g L-1) using PEG-6000. The experiment was arranged factorally in completely randomized design with three replications. Data on germination and growth indices were collected and analyzed using one way ANOVA. The result revealed that highest germination percentage (99.7%), germination rate (14.6 plants day-1) and seedling vigor index (9.67) were obtained from the local cultivar. Progressive increase in water stress had also significantly reduced germination indices. There was no significant difference among the cultivars in producing taller root and shoot length. The local cultivar had significantly produced highest root number (4.3 plant-1), shoot fresh weight (0.214 g), seedling fresh (0.314 g) and dry weight (0.097 g). Even though, all the growth parameters of wheat cultivars showed a diminishing trend with increasing the level of PEG-6000 induced water stress, a highly significant decrease in the parameters were observed starting from 150 g L-1 PEG concentration. Higher shoot length inhibition was observed for Dandaa cultivar followed by Huluka. Hulukas root growth was more inhibited than Dandaa. According to the growth and germination indices results, the local cultivar is the drought tolerant wheat cultivar. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22651 Int. J. Agril. Res. Innov. & Tech. 4 (2): 55-60, December, 2014